An operating strategy for wind-solar-storage hybrid shore power supply systems based on distributionally robust optimization - HUANG Mengqi; LI Yonghui; YANG Jun; LIAO Fei; PENG Yong; LIN Yi (Zhejiang dianli, 2024)
The output of renewable energy units and electric vessels， characterized by its uncertainty and impact， pose challenges to the safe and stable operation of shore power supply systems. To address this， an operating strategy for wind-solar-storage hybrid shore power supply systems based on distributionally robust optimization （DRO） is proposed. First， a deterministic operating model of the shore power supply systems is established with the objective of minimizing total costs， without considering the uncertainty of wind-solar power output and impact loads. Building on this model， a two-stage wind-solar-storage hybrid shore power supply system model based on DRO is developed. This model uses a combinatorial approach to describe the uncertainty of wind-solar power output， aiming to reduce the wind and solar power curtailment caused by prediction errors and output fluctuations. Finally， the column-and-constraint generation （C&CG） method is employed to solve the model. Using data from a specific shore power supply system， the proposed strategy is validated to effectively enhance the consumption capacity of wind-solar resources and reduce operational costs.